The impact of weather on time allocation to physical activity and sleep of child-parent dyads - Ha Trong Nguyen; Hayley Christian; Huong Thu Le; Luke Connelly; Stephen R. Zubrick; Francis Mitrou (Global Labor Organization (GLO), 2021)
This study explores the differential impact of weather on time allocation to physical activity and sleep by children and their parents. We use nationally representative data with time use indicators objectively measured on multiple occasions for more than 1,100 child-parent pairs, coupled with daily meteorological data. Employing an individual fixed effects regression model to estimate the causal impact of weather, we find that unfavourable weather conditions, as measured by cold or hot temperatures or rain, cause children to reduce physical activity time and increase sedentary time. However, such weather conditions have little impact on children's sleep time or the time allocation of their parents. We also find substantial differential weather impact, especially on children's time allocation, by weekdays/weekends and parental employment status, suggesting that these factors may contribute to explaining the differential weather impact that we observed. Our results additionally provide evidence of adaptation, as temperature appears to have a more pronounced impact on time allocation in colder months and colder regions. The results suggest that extreme weather conditions, including those associated with climate change, could make children vulnerable to reduced physical activity.
Keywords: I12; J13; J22; Q54; 330; Weather; time allocation; physical activity; sleep; family; dyad